Neuronal-Activated ILC2s Promote IL-17A Production in Lung γδ T Cells During Sepsis - Chen, Weiwei; Lai, Dengming; Li, Yuehua; Wang, Xueke; Pan, Yihang; Fang, Xiangming; Fan, Jie; Shu, Qiang (Frontiers in Immunology, 2021)
Background Studies have revealed important roles for IL-17A in the development of acute lung injury (ALI) following sepsis. However, the mechanism underlying the regulation of lung IL-17A remains to be fully addressed. Recent studies suggested the effect of neuromedin U (NMU) on immune cell activation and the role of group 2 innate lymphoid cells (ILC2s) in the modulation of IL-17A production. We aimed to gain in-depth insight into the mechanism underlying sepsis-induced lung IL-17A production, particularly, the role of NMU in mediating neuronal regulation of ILC2s and IL-17A-producing γδ T cells activation in sepsis. Methods Wild type mice were subjected to cecal ligation and puncture (CLP) to induce sepsis with or without intraperitoneal injection of NMU. The levels of ILC2s, γδ T cells, IL-17A, NMU and NMU receptor 1 (NMUR1) in the lung were then measured. In order to determine the role of NMU signaling in ILC2 activation and the role of ILC2-released IL-9 in ILC2-γδ T cell interaction, ILC2s were sorted, and the genes of nmur1 and il9 in the ILC2s were knocked down using CRISPR/Cas9. The genetically manipulated ILC2s were then co-cultured with lung γδ T cells, and the levels of IL-17A from co-culture systems were measured. Results In septic mice, the levels of NMU, IL-17A, ILC2s, and IL-17A-producing γδ T cells in the lung are significantly increased, and the expression of NMUR1 in ILC2s is increased as well. Exogenous NMU further augments these increases. The main source of IL-17A in response to CLP is γδ T cells, and lung nmur1 is specifically expressed in ILC2s. In vitro co-culture of ILC2s and γδ T cells leads to increased number of γδ T cells and higher production of IL-17A from γδ T cells, and these alterations are further augmented by septic treatment and exogenous NMU. Genetic knockdown of nmur1 or il9 in ILC2s attenuated the upregulation of γδ T cells and IL-17A production. Conclusion In sepsis, NMU acting through NMUR1 in lung ILC2s initiates the ILC2 activation, which, in turn, promote IL-17A-producing γδ T cell expansion and secretion of IL-17A. ILC2-derived IL-9 plays an important role in mediating γδ T cell expansion and IL-17A production. This study explores a new mechanism underlying neuronal regulation of innate immunity in sepsis.